Vaccine hesitancy among nursing and midwifery undergraduate students in Switzerland: protocol for an online national study - Pouvrasseau, Audrey; Jeannot, Emilien (Frontiers in Public Health, 2023)
Background: Vaccine hesitancy is a persistent challenge in public health, exacerbated by the proliferation of anti-vaccine sentiments facilitated by social networks. The COVID-19 pandemic has underscored the importance of addressing vaccine hesitancy, designated by the WHO as a top global health threat. This study explores vaccine hesitancy among nursing and midwifery undergraduate students in Switzerland -a cohort crucial to public health given their future roles as healthcare professionals -with a particular emphasis on the HPV vaccine, which exhibits lower confidence levels compared to other vaccines.Methods: This study will employ an online questionnaire distributed to nursing and midwifery undergraduate students from various healthcare universities. The questionnaire will collect data on vaccine hesitancy (general confidence in vaccines and specifically in the HPV vaccine), HPV vaccine coverage, socio-demographics, likelihood to recommend vaccines to patients, perception of vaccination education and interest in complementary medicine.The study's findings will contribute to our understanding of vaccine hesitancy among nursing and midwifery undergraduate students, providing insights that can inform targeted interventions and education strategies to bolster vaccine confidence among future healthcare professionals, thereby enhancing public health efforts.